Optimization of Wall-disruption Process of Rose Bee Pollen and Comparison of Physiological Activities of Its Ethanol Extracts - Xinyang LU; Yishu SUN; Tao XU; Longbin FAN; Yaning CHANG; Yingjun ZHOU (Shipin gongye ke-ji)
Rose bee pollen has a pleasant aroma and a sweet taste, and it is rich in polyphenols and other bioactive substances, making it a highly nutritious and promising natural health product. To optimize the enzymatic hydrolysis process for rose bee pollen and to systematically compare the physiological activities and primary component profiles of its different ethanolic extracts. This was done with the aim of discerning the most efficacious extract that possessed significant anti-inflammatory and anti-benign prostatic hyperplasia (BPH) effects. The results demonstrated that the optimal enzymatic hydrolysis process parameters for rose bee pollen were a solid-to-liquid ratio of 1:30, a temperature of 55 °C, pH6, a composite enzyme system addition of 2.0% (cellulase comprising a ratio of 7:5 with composite protease), and a reaction time of 9 h, resulting in the highest wall-disruption rate of 73.13%. The active substances extracted with 90% ethanol could significantly (P<0.01) reduce the release level of inflammatory factors induced by lipopolysaccharide in RAW264.7 cells (at 20 μg/mL, compared with the model group, nitric oxide, interleukin-6 and tumor necrosis factor-α decreased by 67.04%, 16.74% and 21.74% respectively), and had the most obvious inhibitory effect on the activity and proliferation of BPH-1 cells, thus exhibiting optimal anti-inflammatory and anti-BPH effects. This research provides a theoretical basis for identifying the active ingredients in rose bee pollen and further developing value-added processed products.